THE ROLE OF INFORMED CONSENT IN PROVING MEDICAL MALPRACTICE CASES (REVIEW OF INDONESIAN SUPREME COURT'S DECISION No. 233 K/PID.SUS/2021) - Benny Wijaya (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
The State of Indonesia in providing protection for patients who receive medical services, doctors and dentists in carrying out medical practices are required to provide medical services according to professional standards and standard operating procedures in accordance with Indonesian law no. 29 of 2004 article 51 letter a,.Informed consent is one of the requirements that must be met before doctors perform medical procedures on their patients. However, even though there is Indonesian Law No. 29 of 2004, there are still doctors who commit negligence by providing services that are not in accordance with procedures by not asking for approval for medical actions that lead to malpractice claims from their patients.. The research conducted is classified as normative juridical research, using primary legal materials and secondary materials from laws and regulations, court decisions, legal theory, and existing journals as a basis.. The doctor's error by taking actions that are not in accordance with the procedure in the form of without asking for informed consent is an administrative violation so it is categorized as administrative malpractice. Indonesian Supreme Court Decision No. 233 K/PID.SUS/2021 which imposes a prison sentence in an administrative malpractice case on a legal basis that has been declared non-binding by the Indonesian Constitutional Court is an act of carelessness. However, the guilty verdict for the defendant was already correct, because the defendant did not give informed consent before carrying out a risky procedure for his patient